How to explain modern security concepts to your children. Issue 5 (3rd September 2017) - Bultel, Xavier; Dreier, Jannik; Lafourcade, Pascal; More, Malika
ABSTRACT: At the main cryptography conference, CRYPTO, in 1989, Quisquater and colleagues published a paper showing how to explain the complex notion of zero-knowledge proof in a simpler way that children can understand. In the same line of work, this article presents simple and intuitive explanations of various modern security concepts and technologies, including symmetric encryption, public key encryption, homomorphic encryption, intruder models (CPA, CCA1, CCA2), and security properties (OW, IND, NM). The explanations given in this article may also serve in demystifying such complex security notions for non-expert adults.